Desempenho produtivo de cultivares de pereira para o cultivo em regiões subtropicais - Fazenda, Lucídio Henriques Vote (2019)
In recent years, the cultivation of pear (Pyrus sp.) in Brazil had little expansion, which caused the pear to be the second fruit most imported by the Brazilian market. The main producing region of the country is the southern region, where it is explored the European cultivars of medium and high cold necessity (Pyrus communis). In the central and eastern region of the states of São Paulo and Paraná, there are crops of Asian pears (Pyrus pyrifolia), which have low cold needs. On merit of genetic improvement work developed by the Agronomic Institute (IAC) and EMBRAPA Clime Tempered, in the past decades, between European and Asian pear cultivars, some hybrid cultivars were introduced(Pyrus communis x Pyrus pyrifolia)known as rustic pears, which have less need of cold and can be grown in subtropical and tropical regions. However, there is a need to quantify and indicate the cultivars of hybrid pears, Asian pears whose fruits are oval; the bark is greenish; the pulp is crispy rusticity or soft, sweet and very juicy, and even the European ones with qualities of their fruits have piriform shape and are aromatic; the bark may be smooth or russeting and yellowish, reddish or even brownish in color; the pulp is juicy, soft and sweet when ripe, and less cold to regions with a subtropical climate. The objective of this study was to quantify the productive performance of low-need cold pear cultivars for cultivation in subtropical regions. Saplings of 11 cultivars of Pereira ('Shinseiki', Packham's Triumph ',' Willians', 'Triunfo', 'Centennial', 'Seleta', 'Cascatense', 'Le Conte', 'Primorosa', 'D'água' and 'Tenra'). The plants were conducted in a central leader system. In the productive cycles 2015/16, 2016/17, 2017/18 and 2018/19, the phenological description was made: beginning, full and end of flowering and harvest. At the end, the duration of flowering and harvesting were calculated in days. It was also quantified the productive performance (production and productivity) in the four productive cycles, and the quality of the fruits. Having verified that the evaluated cultivars presented variability among themselves in relation to the physical and physical-chemical characteristics, more presented qualities of suitable qualities for the natural consumption, with a higher content of soluble solids, lower titratable acidity, and higher ratio. It was concluded that the cultivars 'Tenra', 'Triunfo', 'Centenária' and 'Seleta' are the most suitable for cultivation in regions with a subtropical climate.